Analysis of the Metal Work Function Dependence of Charge Transfer in Contacted Graphene Nanoribbons - Davide Mencarelli; Luca Pierantoni (Nanomaterials and Nanotechnology)
In this paper, the analysis of charge injection from metal to a contacted graphene nanoribbon (GNR) is developed by means of a scattering matrix approach. The charge transport, described by the Schrödinger equation in the 2D domain of the GNRs, is solved, together with the 3D Poisson equation for the potential distribution. Varying the work function of the metal contacted to the GNR, alters the so‐called “metal doping”, i.e., the amount of charge in the GNR. As easily expected, this in turn affects the I‐V characteristic of a GNR channel across two electrodes. Interesting effects appear as the contribution of GNR sub‐band is considered and included in the selfconsistent calculation.